ANALISIS KESEJAHTERAAN EKONOMI PETANI PADI MELALUI PERTANIAN ORGANIK DI DESA LOMBOK KULON WONOSARI BONDOWOSO - Wilda Tul Uluf (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2024)
Organic farming is an effort to reduce farmers' dependency on chemical fertilizers. Besides the distribution scarcity, chemical fertilizers have been proven to decrease soil fertility, which in turn affects the decline in rice yields. This research aims to determine the improvement in the economic welfare of rice farmers through organic farming and the impact of organic rice farming on the community in Lombok Kulon Village, Wonosari District, Bondowoso Regency. The method used in this research is a qualitative method with a phenomenological approach. Data collection techniques include observation, interviews, and documentation. The data analysis techniques used involve data reduction, data presentation, and drawing conclusions. The results of the research show an improvement in the welfare of rice farmers through organic farming, a positive impact on agricultural land that uses organic farming, and the development of organic tourism villages that have a positive impact on the community.